Seroprevalence and Molecular Detection of Brucellosis in Hospitalized Patients in Lahore Hospitals, Pakistan - Yousaf, Riffat (Infect Dis Rep, 2021)
Brucellosis is one of the most notorious zoonoses worldwide. The disease is common and endemic in humans and animals of Pakistan, but lack of awareness and lack of research have resulted in an increased incidence in the human population. The present study aimed to determine the seroprevalence and at molecular detection of brucellosis in patients with clinical symptoms in six different hospitals from Lahore, which is the capital city of Punjab province. A total of 218 blood samples were collected from hospitalized patients. The samples were initially screened by the Rose Bengal Plate Test (RBPT), and then quantitative real-time PCR (qRT-PCR) was applied. An overall seroprevalence of 17% (37/218) was found. The highest prevalence was found at the Lady Health center (36.53%), which was followed by the Lady Willingdon Hospital (28.6%). Female patients showed a higher seroprevalence than males and peaked at 34% (n = 32) for women who suffered from abortion. In total, 16.8% of patients younger than 30 years showed seropositive reactions, while the prevalence was 19% in patients between 31 and 50. Thirty-three DNA samples from 24 seropositive and nine seronegative patients tested positive, 32 samples were found positive for B. abortus DNA, and one sample failed to be identified at the species level. Almost all positive cases had direct contact with animals and consumed unpasteurized dairy products. Research on human brucellosis is still scarce in Pakistan. For the diagnosis of brucellosis, serology and molecular tools should be combined if isolation by culture is not possible. Nationwide control activities and increasing awareness for zoonotic brucellosis are needed.